Digital Design & Additive Manufacturing Technology at POLMAN Bandung - Ismet P. Ilyas (International Conference on Industrial Revolution for Polytechnic Education, 2019)
New Industrial Revolution era is in progress.Digitalization and the implementation of the extended enterprisesare becoming new playground and have become strategies tosurvive. Based on these, it comes into view that PoliteknikManufaktur (POLMAN) Bandung education orientation - morepractical and business oriented - have to actively participate andplay its role in industrializing the nation. The current and futurecompetitiveness of national manufacturing industries requirehighly educated and motivated manufacturing professionals astheir capabilities are also critical to the viability of the industries.Concerning these, POLMAN Bandung has been constructed itselfas a part of major drivers that can play important roles andparticipate in promoting excellence for national manufacturingindustries, leveraging industry competitive advantages, and at theend leveling up national economic in order to cope with thechallenges in industrial revolution today and the years to come.One of the POLMAN’s strength is the deployment of a DigitalDesign and Additive Manufacturing Technology (DDAMT), whichconsidering plays a crucial role and one of the key strategies of themanufacturing industries in setting up vision and strategicplanning toward the IR 4.0 and beyon. The idea of the DDAMTdeployment at POLMAN Bandung is challenged by the rapidlychanges of the Information and Communication Technology (ICT)application and the global manufacturing trends for the effectiveand efficiency operations in global hubs and networks. This paperwill discuss a specific implementation of the DDAMT at POLMANBandung. The discussion gives emphasis to the way in whichPOLMAN Bandung carries out manufacturing education bymeans of the DDAMT. Being implemented in the last two decades,the DDAMT at POLMAN Bandung has shown its quality as apromising learning tools for integrating a ‘real’ industryenvironment with the education concept. To get moreunderstanding, this paper briefly describes POLMAN experiencesregarding to the DDAMT in three sections: the introduction, theadvantages and benefits that need to be considered, and theoverview the challenges as well as opportunities toward theapplications. The strategic aspects and needs of the DDAMT inresearch, design and development are main concerns of thepresentation